Evaluation of knowledge and Satisfaction among service recipient of (Integrated Management of Neonatal and Child Health Program) in Primary Health Care Centers in Baquba City - Khalid Abdullah, Mazin; Hussein Bahir, Basim; Kahtan , Oday (Diyala Journal of Medicine, 2023)
Background: Integrated Management of Neonatal and Child Health Program (IMNCH) is an approach to offering solid evidence. It is used as a strategy to draw national and international investment into many initiatives to improve child health because it is diagnostically superior to conventional routine practice. Objective: To assess the knowledge and satisfaction rate among Integrated Management of Neonatal and Child Health Program care takers. Patients and Methods: A cross sectional study was conducted in two sectors (The health care sector in baqubah first and second) that offers health services in Baquba city from 15th December 2015 to 1st of June 2016. A convenient sample of 150 cases were included in the study from the age of two month to five years. Data collected by special designed questionnaire that adopted from world health organization. Results: The result showed that 87.3 % of health providers prescribed oral medicine for child out of them 86.3% of service recipient know how many times day that should be given while 25.2% of them know how many days that should be given. oral rehydration solution was prescribed 31.3% of children majority of health takers 87.2% known quantity of water to maxed with one sachet of ORS Showed that 24.7% of service recipients bring back the child immediately to primary health care center when the child unable to drink or breast feed and 23% of service recipients bring back the child immediately when the child becomes sicker or develop fever or difficult breathing and 30%when the child breathing is fast or difficult breathing and 18% of service recipient were satisfied about care that provided for children while 82% of service recipients were not satisfied. Conclusion: The satisfaction rate of service recipients about the service that provided in primary heath care center in Baquba city were poor.